Hubungan Konsep Diri Dengan Komunikasi Interpersonal Pada Mahasiswa Theologia di Sekolah Tinggi Theologia (STT) Paulus Medan - Diaken Eklesia Sumbayak; Mustika Tarigan; Eryanti Novita (Jouska: Jurnal Ilmiah Psikologi, 2022)
This study aims to examine the relationship between self-concept and interpersonal communication on students at the Paul Theological School of Medan. This study uses a quantitative approach with product moment correlation test. The variables in this study are self-concept and interpersonal communication. The population of this study amounted to 80 people and the research sample also amounted to 80 students of the Paul Theological School of Medan Forces 2016-2018. The data collection technique used in this study used a questionnaire with a Likert scale. The results of the validity test showed that the self-concept variable contained 5 invalid statements and 35 valid statements, while the interpersonal communication variable contained 5 invalid statements and 41 valid statements. Based on the results of testing the condition of self-concept, the results show that the level of self-concept is at a positive level and interpersonal communication variables are at a positive level. Based on the calculation of Product Moment Correlation, it is known that there is a significant positive relationship between Self-Concept and Interpersonal Communication, with (Rxy = 0.640; p= 0.000 0.050). From the results of this correlation, it can be stated that the hypothesis proposed in this study is accepted, namely the better the self-concept, the higher the Interpersonal Communication. The determinant correlation test (r^2) of the relationship above is = 0.410, this shows that interpersonal communication is influenced by self-concept by 41%. Thus, self-concept contributes to improving interpersonal communication.